Comparative Study of Suicide Methods During 1991-2008 in the Ulaanbaatar Community - Davaasuren, Oyunsuren; Zuunnast, Khishigsuren; Naidansuren, Tuya (Central Asian Journal of Medical Sciences, 2016)
Objectives: The purpose of our study is to compare the prevalence and the methods used for fatal suicidal behaviors among the population in Ulaanbaatar, Mongolia. Methods: A descriptive and retrospective study was conducted based on all data related to fatal suicidal behaviors among the Ulaanbaatar community through reanalysis of secondary data from two epidemiological studies. Results: Totally, 3498 fatal suicide cases were recorded among the Ulaanbaatar population in 1991-2008. Most of the fatal suicide cases (85.1%) were males and 71.6% of the total respondents strangled oneself for fatal suicide, making strangulation the most commonly-used suicide method. Fatal suicide cases due to acute alcohol intoxication (4.6%) or committing suicide while being drunk (3.0%) were recorded in 1991-2002, but were not recorded during 2003-2008. For the fatal suicide cases, being strangled from the ger toono accounted for 12.9% of the total strangulation cases and it was a specific characteristic for Mongolia. More 18-34 year-olds were registered as fatal suicide casesthan other age groups (40.7% in 1991-2002 and 53.3% in 2003-2008). Condusion:ln Ulaanbaatar, the group most likely to complete suicide was 18-34 year-old males, therefore intervention strategies to reduce suicide in Mongolia should focus particularly on this group.